HIV, sex and sexuality in later life - Henrickson, Mark; Dryden, OmiSoore H., 1965- (Sex and intimacy in later life, 2023)
Following the development of anti-retroviral therapies (ARVs), many people affected by HIV in the 1980s and 1990s have now been living with the condition for decades. Drawing on perspectives from leading scholars in Bangladesh, Canada, Hong Kong, New Zealand, Switzerland, Ukraine, the UK and the US, as well as research from India and Kenya, this book explores the experiences of sex and sexuality in individuals and groups living with HIV in later life. Contributions consider the impacts of stigma, barriers to intimacy, physiological sequelae, long-term care, undetectability, pleasure and biomedical prevention (TasP and PrEP). With the increasing global availability of ARVs and ageing populations, this book offers essential future directions, practical applications and implications for both policy and research.